Assessment of mental health outcomes and associated factors among workers in community-based HIV care centers in the early stage of the COVID-19 out- break in Mali (2020)
As of July 14, 2020, the COVID-19 case-fatality rate in Mali was the fifth highest in the World Health Organization’s (WHO) African region, and the third highest among West African countries, with deaths representing 5.0% of total cases behind 6.2% and 5.1% in Niger and Burkina Faso, respectively [1]. The first cases in Mali were observed on March 25, 2020, over a month after the continent’s first case, and 6 and 16 days after the two abovementioned countries, respectively. However, the number of cumulated cases in Mali was much higher up to July 14: 2423 cases versus 1037 and 1099 cases in Burkina Faso and Niger, respectively [1]. The lag between Africa’s first cases and those in Mali did not create the same opportunity - in terms of prompt emergency preparation - which the lag in 2014 created during the Ebola outbreak. Moreover, international aid has slowed down because of COVID19’s pandemic status. Data for Mali indicate that authorities’ proactive decisions to contain the disease’s spread, including commercial air traffic interruption, bans on mass gatherings and curfews, [2] have been insufficient. Furthermore, as observed elsewhere, the public health response is being undermined by poor adherence to social distancing for different reasons [3,4]. However, the most likely explanation for Mali’s higher vulnerability and poorer medical outcomes is its inherently weak healthcare system. Compared with Niger and Burkina Faso, the shortage of healthcare workers (HCW), health expenditures and infrastructure is more acute in Mali [5]. More specifically, the country’s dependency on foreign aid, unreliable medical equipment, difficulties to procure drugs [6], staff attrition [7], shortage of human resources (HR) [8,9] and resulting degradation of working conditions - including increased workload [10–12]- all contribute to putting HCW who are on the front line fighting COVID-19 under greater stress. Added to this is the fact that care for COVID-19 is only concentrated in 6 hospitals (5 in Bamako and 1 in Kati (19 Km from Bamako)) positioned at the top of the country’s 4- level healthcare pyramid [13]. The deleterious impact on HCW mental health [14,15] because of the these structural problems and unpreparedness to contain COVID-19 constitutes a serious public health issue [16]. Unfortunately, data about mental health among HCW in Mali is inexistent. However, the WHO asserts that increasing terrorism and insecurity in Mali since 2012 are two factors that could have mental health implications for the general population [17], and therefore this would include HCW.